CHEMICAL AND SENSORY QUALITY CHANGES IN WILD AND FARMED FISH FLESH (LABEO ROHITA) AT FROZEN STORAGE (-18°C) - S. Alam; N. Khan; M. Nasir; A. Javid; T. A. Khan; R. Tayyab; N. Zikria (Journal of Animal and Plant Sciences, 2012)
A study was conducted to evaluate the effect of frozen storage (-18 ˚C) on the chemical and sensory quality of wild and farmed fish flesh (Labeo rohita). Ten fish with an average weight of about 700-1000 g were collected each from Head Balloki (wild) and University of Veterinary & Animal Sciences, Pattoki Fish Farm. Fish fillets were prepared and studied for chemical composition and sensory attributes at 1st, 15th and 30th day of frozen storage. The design of the experiment was completely randomized and the significance was assessed through two way (site & study duration) ANOVA technique. Farmed fish was found significantly higher (P ≤ 0.05) in dry matter (92.52%) than wild fish (90.51%). Ash contents were found (7.34%) in wild fish and (7.04%) in farmed fish.  Ash contents were significantly higher on the first day followed by 15th day and 30th day. The crude fat contents of fish on 30th day were significantly higher than 1st and 15th days. Crude protein contents of wild fish was (80.29%) and (79.93%) in farmed fish. A non-significant difference (P ≥ 0.05) among farmed and wild fish was observed. The storage intervals significantly affect protein contents on 15th and 30th day. In case of sensory attributes, colour, flavor, tenderness and overall quality of farmed fish was observed significantly higher compared to wild fish. Storage intervals also significantly affect the sensory attributes such as colour, flavor, juiciness, tenderness, oiliness and overall quality. These attributes were found significantly higher up to 15th days than 30th day of storage which deteriorates the product sensory attributes and overall quality. In conclusion, it has been observed that wild fish was richer in fat contents than farm fish and the storage intervals significantly affect/deteriorate the product quality after keeping more than 15th days at -18 ˚C. However, the effects of frozen storage on chemical and sensory quality changes need further long term investigation.
Keywords: Chemical composition; Labeo rohita; Sensory attributes; Wild and farmed fish flesh